Knowledge and Attitude of Paramedical Staff Towards COVID-19 Vaccine in Babylon City - Noor Abdulwahid Abbood; Sally Alaa Kareem (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Several vaccines against coronavirus disease (COVID-19) have been licensed and are being distributed globally in various regions. The general population’s knowledge, and attitudes of COVID-19 vaccinations, on the other hand, are poorly understood. Subjects and Methods: This study is a descriptive; cross sectional study conducted at 4 hospitals and primary health care sectors in Babylon City. The Data were collected by direct interview with the paramedical staff by the researcher, by using a self-reporting questionnaire form. Results: The current study showed that the highest proportion of paramedical staff, 28% in Imam Al-Sadiq Hospital. The mean ± SD of their ages was 36.3±15.7 years, the age range at the time of study was between (19-59) years. The study found that 50.25% of participants were single and for Job title, distribution of Medical assistant constitutes were 40% of participants. Conclusions: We conclude that most paramedical staff had good scores for knowledge and attitude towards Covid-19 vaccine, despite found poor scores for some participants.